Herbicide selectivity for açaí palm (Research, Society and Development, 2025)
The açaí palm (Euterpe oleracea, Arecaceae) is a palm tree native to the Amazon, traditionally exploited in the extractive system and whose fruits are used to produce a beverage known as açaí wine. Due to increasing consumption, extractivism does not meet the increased demand and the açaí palm has begun to be cultivated in upland areas in the Amazon region. The weed interference is a factor that impairs plant growth and fruit production in upland, requiring periodic control. Weed control with herbicides has the advantages of obtaining high control efficacy, lower cost, greater operational performance and less dependence on labor. Selective herbicides control weeds and do not impairs the açaí palm tree; however, evaluations are necessary for the safe use of herbicides. Thus, this study aimed to evaluate the selectivity of the herbicides 2,4-D dimethylamine (670, 1005, 1340 and 1675 g), diuron (750, 1250, 1750 and 2250 g), fenoxaprop-p-ethyl (55, 82.5, 110 and 137.5 g), metribuzin (240, 480, 720, 960 g) and sulfentrazone (500, 750, 1000 and 1250 g). The experiment was conducted in nursery conditions in pots with açaí seedlings (BRS Pai d’Égua) at the growth stage of five fully expanded leaves. 2,4-D, diuron, metribuzin and sulfentrazone were applied under the canopy of the seedlings and fenoxaprop-p-ethyl on the leaves. All herbicides at all doses were selective for the açaí palm, with phytotoxicity considered mild.